Learning path : Being a better introvert. - Zack, Devora; Kahnweiler, Jennifer B.; Ford, Neal; Richards, Mark; Safari eBooks ([Place of publication not identified] : O'Reilly, 2015)
"Learn how to network in social situations, gain confidence when speaking in groups and to strangers, and realize how important people skills are to your daily job, even if you aren't in a technical role."--Resource description page.
Networking for people who hate networking : a field guide for introverts, the overwhelmed, and the underconnected / Devora Zack -- Success skills for introverts : cultivating quiet strengths / Jennifer Kahnweiler -- Software architecture fundamentals Part 4 : soft skills : leadership, negotiation, meetings, working with people & building a tech radar / Neal Ford and Mark Richards.
Presenters, Devora Zack, Jennifer Kahnweiler, Neal Ford and Mark Richards.
Title from resource description page (viewed May 25, 2016).
Date of publication from title screen.
Keywords: Interpersonal communication; Interpersonal relations; Public speaking; Business communication; Business networks; Electronic books